INTERMEDIASI, STRUKTUR MODAL, EFISIENSI, PERMODALAN DAN RISIKO TERHADAP PROFITABILITAS BANK - Djamil thalib (University of Merdeka Malang, 2016)
AbstractThis study aimed to analyze the causality between intermediation as measured by the LDR, capitalstructure measured by DER, efficiency as measured by ROA, capital measured by CAR and NPL to quantifythe risk to profitability. This study took a sample of 25 banks listed on the Indonesia Stock Exchange period2008 to 2013, with a purposive sampling method. The data analysis technique multiple linear regressionmodel. The results showed that the LDR, DER, CAR positive effect on profitability. While ROA and NPLinfluenced by the negative direction towards profitability.